2007
DOI: 10.1007/s10529-007-9501-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinduction in human fat-derived stem cells by recombinant human bone morphogenetic protein-2 produced in Escherichia coli

Abstract: Bioactive recombinant human bone morphogenetic protein-2 (rhBMP-2) was obtained using Escherichia coli pET-25b expression system: 55 mg purified rhBMP-2 were achieved per g cell dry wt, with up to 95% purity. In murine C2C12 cell line, rhBMP-2 induced an increase in the transcription of Smads and of osteogenic markers Runx2/Cbfa1 and Osterix, measured by semi-quantitative RT-PCR. Bioassays performed in human fat-derived stem cells showed an increased activity of the early osteogenic marker, alkaline phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…In this study, the system of gelatin hydrogels for combined release of SDF-1 and BMP-2 synergistically enhanced bone regeneration. SDF-1 has an inherent ability to enhance the recruitment of hematopoietic cells [14e17] and BMP-2 has a potential to promote the osteogenic differentiation of bone progenitor cells [20,21] and to recruit the cells [8,9]. If the release of two protein factors works well, it is theoretically possible that the recruitment of hematopoietic and bone progenitor cells will be promoted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the system of gelatin hydrogels for combined release of SDF-1 and BMP-2 synergistically enhanced bone regeneration. SDF-1 has an inherent ability to enhance the recruitment of hematopoietic cells [14e17] and BMP-2 has a potential to promote the osteogenic differentiation of bone progenitor cells [20,21] and to recruit the cells [8,9]. If the release of two protein factors works well, it is theoretically possible that the recruitment of hematopoietic and bone progenitor cells will be promoted.…”
Section: Discussionmentioning
confidence: 99%
“…Among osteogenic growth factors, bone morphogenetic protein-2 (BMP-2) is well-known as a strong inducer of bone tissue formation by enhancing the recruitment of osteoblast progenitor cells [8], angiogenesis [19], and promoting the osteogenic differentiation of mesenchymal stem cells [20,21]. The BMP-2 treatment induced complete bone regeneration at a bone defect [22] and formed bone tissues ectopically for the animal models [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In early studies, the poor efficacy of ErhBMP-2 was thought to be due to the inefficient refolding process of the BMP-2 protein after expression in E. coli [15]. In recent years, successful methods for restoring the biologic activity after rhBMP-2 expression in E. coli have made it possible to produce fully functional BMP-2 from E. coli [10,24]. In addition, it was shown that post-translational glycosylation was not critical for a fully functional ErhBMP-2, because the basic glycosylated N-terminal domains of rhBMP-2 were not obligatory for receptor activation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Fat-derived stem cells have been used in the repair of bone (Bessa et al, 2008;Betz et al, 2010), and are regarded as potentially suitable for the repair of soft-tissue defects (Vallée et al, 2009). Applications to the repair of airway defects are, however, so far few.…”
Section: Gm Roomansmentioning
confidence: 99%